NEW MEDIA: ISLAM AGAINST GLOBAL PROPAGANDA (ANTITHES AGAINST ISLAMOPHOBIA IN SOUTHEAST ASIA) - Salman Alfarisi; Mailin Mailin (Universitas Dharmawangsa, 2021)
Abstract Reporting of terrorist acts in Indonesia has always been a hot topic of discussion. When reporting on the action related to radical Islamic groups automatically appears a negative stigma against Islam. The negative stigma presents Islamophobia and becomes a topic of discussion on social media that affects social and political interpretations of society. All feel entitled to provide views, comments, feedback and attitudes and seek to influence each other. Some Islamic teachings or terminology are stigmatized as the cause of the birth of acts of terror. Among them, the debate over the terminology of